THE INFLUENCE OF DOPING FE ON TIO2 PHOTOANODES FOR PEROVSKITE SOLAR CELL (PSC) STUCTURE SYTHESIS : COMPREHENSIVE REVIEW - Iman Faisal, Hanif
Sustainable energy development strategies typically involve three major technological changes, namely energy savings, improvement efficiency of energy production, and replacement of fossil fuels as main energy input. Solar cell is one of many renewable energy sources that able to maximize energy needs in developing countries. Solar cell generation potentially developed is perovskite solar cell (PSC). PSC is 3rd generation of solar cell utilizing perovskite material as light absorbing materials. Primary cell components of PSC consist of photoanode, perovskite, holes transport layer, and metal electrode. Photoanode in PSC acts as a transmission electron generated layer from the perovskite to external circuit to generate electric energy. TiO2 is the best electron transporting material applied in PSC due to high photocatalyst activity. However, high charge recombination in TiO2 can degrade PSC performance In this literature, manipulation of characterization TiO2 by doping Fe aims to optimize power conversion efficiency of PSC. The literature study is carried out by analyzing various information that related to characterization result of perovskite solar cell using Fe doped TiO2 as photoanode for synthesizing structure and optimizing TiO2 synthesis process in order to increasing PSC performance. The data on changing characterization of TiO2 after adding Fe dopant is collected and analyzed the influence on alteration PSC power conversion efficiency. The result of data collection and analysis information from various literatures show doping Fe in TiO2 is affecting structure and band gap energy of TiO2 and PSC performance. In working to enhance conversion energy efficiency in PSC, it is necessary to optimize the synthesis process parameter of TiO2 layers and content of Fe dopant in TiO2. PCE of perovskite solar cell is increased by doping Fe 1%mol in TiO2 due to alteration TiO2 characteristic, namely decreasing crystallite size and band gap energy TiO2 resulting in decreasing charge carrier recombination. Increasing Fe content in TiO2 further can alleviate PCE due to formation of oxide on surface TiO2 that acts as recombination center.